The Effect of Brand Color Emotions and Perceived Value on Brand Association (Study on Somethinc Consumers) - Nabila Nurul Alizha; Popy Rufaidah (Sekolah Tinggi Manajemen IPMI, 2025)
A brand is considered successful when it experiences significant growth and development. However, to achieve this, the brand must excel when compared to other brands. Brand association is believed to be one of the important factors in optimizing brand excellence, as it shapes perceptions, images, beliefs, experiences, feelings, and thoughts that consumers associate by a product. Brand associations that are created are generally related to brand color emotions and perceived value. The beauty industry,experiencing rapid growth and competitiveness, requires optimizing the framework of brand color emotions and perceived value to remain resilient in the market, and Somethinc is no exception. The method used is based on quantitative analysis by the PLS-SEM technique, involving 138 respondents. Data collection is conducted through questionnaires using a Likert scale. The results demonstrated a significant influence of brand color emotions and perceived value on brand association. Modeling results show that 73.8% of brand association can be described by brand color emotions and perceived value, by the remainder described by other variables. Data collection is done by questionnaire by relying on a Likert scale. The results revealed a significant influence of brand color emotions and perceived value on brand association. Modeling results show 73.8% of brand association can be described by brand color emotions and perceived value, while the rest can be described by other variables.